Efficacy of Lurasidone in First-Episode Psychosis: Patient Phenotypes, Dosage, and Recommendations from an Expert Panel - Miquel Bernardo; Marina Díaz Marsá; Ana González-Pinto; Manuel Martín Carrasco; Víctor Pérez Sola; Pilar Alejandra Sáiz; Eduard Vieta; Marta Torrens; Celso Arango; Benedicto Crespo-Facorro (Neurology and Therapy)
Abstract Introduction For patients with psychosis, early, intensive therapeutic intervention is thought to improve long-term outcomes. Furthermore, patients with a first-episode psychosis (FEP) who experience a good early response to antipsychotic medication show a clinical and functional benefit over the longer term if they continue low-dose antipsychotic treatment. Lurasidone is an atypical antipsychotic agent which is approved in Europe for the treatment of schizophrenia in adults and adolescents (13–17 years). The efficacy and tolerability of lurasidone have been demonstrated in both antipsychotic-naïve and previously treated patients. Areas Covered This paper provides a review and commentary regarding the use of lurasidone in patients with FEP. Case studies based on the authors’ clinical experiences with lurasidone in real-world practice are provided. Expert Opinion In our experience, lurasidone has shown efficacy in FEP in different patient profiles, including those with psychoses associated with substance use disorders. Lurasidone provides clinically relevant benefits, especially in patients with affective symptomatology, and has a good tolerability profile.